Morphine and Rapid Disease Progression in Nonhuman Primate Model of AIDS: Inverse Correlation Between Disease Progression and Virus Evolution - Rivera-Amill, Vanessa (2009)
HIV and simian immunodeficiency virus (SIV) have a formidable capacity for mutation and adaptation, a characteristic that has contributed to the extensive genetic variability. Evolutionary pressures imposed within the host and the viral capacity to mutate lead to the generation of such variants. To date, very little information is available regarding the evolution of HIV with drug abuse as a cofounding factor. Using our macaque model of drug dependency and AIDS, we have investigated the dynamics of SIV mutations in the genes tat, vpr, envelope, and nef. The results presented in this review, from our laboratory and others, contribute to the overall understanding of how drugs of abuse might influence immune selective pressure contribution to variation in different SIV genes. Additionally, the studies presented could help enlighten the development of HIV vaccines that take into consideration viral diversity.